Examining the Role of Customer Experience and Perceived Value in Driving Repurchase Intention: The Mediating Effect of Customer Satisfaction on KAI Access Users - Septiana Putri; Ali Maskur (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines the role of customer experience and perceived value in driving repurchase intention, with customer satisfaction as a mediating variable among KAI Access application users. Using a quantitative approach, the study surveyed 150 purposively selected respondents who had purchased tickets at least 3 times in the last 6 months. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS. The results indicate that customer experience significantly affects customer satisfaction (β = 0.519; t = 5.048; p < 0.001), and perceived value also positively affects customer satisfaction (β = 0.338; t = 2.978; p = 0.003). However, customer experience does not significantly influence repurchase intention (β = 0.116; t = 0.866; p = 0.386), and customer satisfaction also shows no significant effect on repurchase intention (β = 0.265; t = 1.923; p = 0.055). In contrast, perceived value significantly influences repurchase intention (β = 0.375; t = 3.396; p = 0.001). Furthermore, mediation analysis confirms that customer satisfaction does not mediate the relationship between customer experience and perceived value toward repurchase intention. These findings suggest that in utilitarian digital transportation services, repurchase behavior is primarily driven by rational value considerations rather than emotional experience or satisfaction. In practice, PT Kereta Api Indonesia should prioritize improving functional value through efficient service features, pricing strategies, and system reliability to strengthen customer repurchase intentions.